High‐Efficiency Infrared Sensing with Optically Excited Graphene‐Transition Metal Dichalcogenide Heterostructures. Issue 31 (8th July 2022) - Kakkar, Saloni; Majumdar, Aniket; Ahmed, Tanweer; Parappurath, Aparna; Gill, Navkiranjot Kaur; Watanabe, Kenji; Taniguchi, Takashi; Ghosh, Arindam
Abstract: Binary van der Waals heterostructures of graphene (Gr) and transition metal dichalcogenide (TMDC) have evolved as a promising candidate for photodetection with very high responsivity due to the separation of photo‐excited electron–hole pairs across the interface. The spectral range of optoelectronic response in such hybrids has so far been limited by the optical bandgap of the light absorbing TMDC layer. Here, the bidirectionality of interlayer charge transfer is utilized for detecting sub‐band gap photons in Gr‐TMDC heterostructures. A Gr/MoSe2 heterostructure sequentially driven by visible and near infra‐red (NIR) photons is employed, to demonstrate that NIR induced back transfer of charge allows fast and repeatable detection of the low energy photons (less than the optical band gap of the TMDC layer). This mechanism provides photoresponsivity as high as ≈3000 A W −1 close to the communication wavelength. The experiment provides a new strategy for achieving highly efficient photodetection over a broad range of energies beyond the spectral bandgap with the 2D semiconductor family. Abstract : This work exploits the bidirectionality of interlayer charge transfer in graphene‐transition metal dichalcogenide heterostructures and demonstrates a reverse charge transfer mechanism to detect sub‐bandgap NIR photons. This novel mechanism allows fast and repeatable detection of low energy photons (< E g ) with a photoresponsivity as high as ≈3000 A W −1 close to the communication wavelength.